2009
DOI: 10.1192/bjp.bp.108.050906
|View full text |Cite
|
Sign up to set email alerts
|

International and indigenous diagnoses of mental disorder among Vietnamese living in Vietnam and Australia

Abstract: Cultural factors in the expression of mental distress may influence the prevalence rates of mental disorders reported across countries. The findings have implications for assessing mental health needs at an international level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 28 publications
2
60
1
Order By: Relevance
“…However, this finding contrasts international studies showing substantially lower rates of common mental disorders in Eastern Asia as compared to English-speaking counties of the West [20,21]. These studies have mainly used Western culturally developed instruments such as the Composite International Diagnostic Instrument (CIDI), and it has been recommended that culture-specific expressions of mental distress should be included when studying mental disorders across ethnic diverse groups [18]. Consequently, we cannot exclude the existence of culture-specific Sami expressions of mental stress not captured by HSCL 10.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, this finding contrasts international studies showing substantially lower rates of common mental disorders in Eastern Asia as compared to English-speaking counties of the West [20,21]. These studies have mainly used Western culturally developed instruments such as the Composite International Diagnostic Instrument (CIDI), and it has been recommended that culture-specific expressions of mental distress should be included when studying mental disorders across ethnic diverse groups [18]. Consequently, we cannot exclude the existence of culture-specific Sami expressions of mental stress not captured by HSCL 10.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, the Vietnamese surveys also applied the Phan Vietnamese Psychiatric Scale (PVPS) designed to identify culturally relevant idioms and expressions of psychological distress in the Vietnamese ethnic group. Inclusion of PVPS mental disorders increased the prevalence rates to 8.8% in the Mekong survey and to 11.7% for the Australian Vietnamese [18]. Another rating-scale adapted to indigenous people is The Kessler Psychological Distress Scale (K10).…”
Section: Introductionmentioning
confidence: 99%
“…70 Therefore, it is important to understand culture-specific ways to express mental symptoms. 72 Consensus or guidelines must be proposed for the estimation of depression and anxiety levels in IBS patients from different cultural backgrounds, so cultural heterogeneity can be overcome. In general, higher prevalence among women was not limited to IBS, but pertained to anxiety and depression as well.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Dissimilar cultural norms, a lack of consistent definitions across cultures for mental illness, collectivistic cultural factors such as loss of face, acculturation, and ethnic identity could contribute to such differences. [14,15,17] Whatever the exact reasons for the under-reporting of psychological distress, the subgroup of GAD sufferers with ''ego-syntonic'' worry has research implications. They indicate that research instruments that explicitly ask respondents if they personally believe their worry to be excessive may not capture all individuals with pathologically excessive worry.…”
Section: Discussionmentioning
confidence: 98%
“…Second, cross-cultural research has indicated that Asians are less likely to spontaneously report psychological distress and to seek treatment for depression and anxiety than their Caucasian counterparts. [14][15][16][17] Although research on cross-cultural differences in the presentation of mental disorders has focused predominantly on depression, a recent study of DSM-IV GAD patients in Nepal and the U.S. further indicated that Nepali patients had higher levels of somatic symptoms and lower levels of psychological symptoms (as measured by the somatic and psychological subscales of the Beck Anxiety Inventory) than American patients with GAD. [18] Third, the determination of excessiveness in the two U.S. studies was based only on one item in the WMH-CIDI that depended on a respondent's subjective and explicit report of whether he/she worried excessively.…”
Section: Introductionmentioning
confidence: 97%